Submerged Floating Tunnel Bridge (SFTB): A Status Report and Evaluation of Technology Readiness Level (TRL) - Nurcahya Nugraha; Jamiatul Akmal; Asnawi Lubis (Journal of Integrated and Advanced Engineering (JIAE), 2022)
One of the problems in archipelagic countries is the land transportation system that has not been integrated between islands. In a relatively wide strait and with a high level of depth, it is impossible to build a bridge. In this case, a submerged floating tunnel bridge/SFTB would be an effective choice. SFTB is an underwater tunnel transport route submerged between the seabed and the surface. Known as the "Archimedes Bridge", the basic principle is balancing buoyancy and tension in the mooring cables. Previous studies on SFTB are still in the form of theoretical concepts and ideas. Further research is needed in all relevant sub-topics to actualize the SFTB. This article reviews previous studies, which are grouped into three sub-topics : (1) materials and construction, (2) dynamic analysis, and (3) feasibility/sustainability studies. At the end of this article, a list of research topics that need further study is presented.